Kerentanan Kerja pada Pekerja Harian Lepas di Industri Kreatif Indonesia - Ayulia Amanda (Journal Research of Management, 2024)
Freelancers in Indonesia is often associated with informality and flexibility, leading to work precarization problems, such as low income and lack of social security. This research explores freelancers' perceptions and experiences regarding work precarization in Indonesia's creative industry. This research uses qualitative methods with an interpretive paradigm and is analyzed with thematic analysis. This research uses semi-structured interviews with 11 freelancers. This research shows that freelancers generally feel vulnerable because their employers ignore their normative rights, there is no legal certainty, their income fluctuates, and they tend to exploit themselves. Specifically, three themes emerged for discussion: job insecurity, job uncertainty, and job injustice. Considering that research on the issue of work precarization for Indonesian freelancers is still limited, a future research agenda could examine one of these three themes in more depth.